A tempestividade da prestação da tutela jurisdicional como requisito essencial à efetividade do direito - Camargo, Bárbara Galvão Simões de [UNESP] (2014)
This dissertation aims to analyze the influence of the timing of the provision of judicial guardianship on the effectiveness of the law. Search to prove the hypothesis that the provision of judicial guardianship in a reasonable time is an essential requirement to the effectiveness of substantive law. Indicates the evolution from the Modern State to the Social and Democratic State of Law. Contextualizes the fundamental rights in a democratic state. Analyzes access to justice and determines their ways of accessibility as well as scores forward in its concept. Studies the history of the emergence of the principle of reasonable duration of the process, its evolution and constitutionalization. Points the treatment of reasonable duration of process adopted in international organizations and the State's responsibility in the international sphere in the case of non-compliance with this principle. Emphasizes the need for adequate time for life and process. Distinguishes the procedure swiftness of reasonable duration of the process and outlines its conceptualization. Relates the principle described in subsection LXXVIII, Art. 5 of the Federal Constitution to due process. Informs the essentiality of observing the principle of efficiency in the conduct of the proceedings and the administration of justice. Confirms that only legislative changes are not sufficient to reduce processing delays. Shows the effectiveness procedural and material. Highlights that judicial slowness is reality that accompany the country since its birth despite scholars assert the existence of a crisis. Research on the influence of the inapplicability of the reasonable duration of the process in jurisdictional confidence in the judiciary. Works with tort liability of the State, supporting the possibility of joining with jurisdictional lawsuit against the State to be reimbursed for materials and/or moral undue damages arising from delay in...